HPB P42 Investigating Factors Associated with Favourable Pathological Tumour Regression After Neoadjuvant Chemotherapy in Patients with Pancreatic Ductal Adenocarcinoma. (7th December 2022) - Halle-Smith, James; Leung, Prudence; Roberts, Keith
Abstract: Background: Neoadjuvant chemotherapy (NAT) is increasingly used in the management of pancreatic ductal adenocarcinoma (PDAC). Pathological response of the tumour to NAT can be assessed using grading systems such as the College of American Pathologists (CAP) system, with favourable regression being associated with improved survival. The aim of the study was to investigate factors associated with favourable tumour regression in patients undergoing pancreatoduodenectomy (PD) for PDAC Methods: Patients who received NAT before undergoing PDAC resection at our institution between 2012 and 2020 were reviewed. Interactions between chemotherapy, tumour staging, carbohydrate antigen 19–9 (Ca19–9) levels, perioperative factors and pathological tumour regression grading (TRG) were explored. Results: 27 patients were suitable for inclusion with a median follow-up of 17.9 months. 7 (26%) patients had a favourable response to NAT. Demographic details and initial tumour staging was similar between the groups. There was a significant difference in the change in Ca19–9 levels from the start of NAT to the end of NAT between the favourable and non-favourable TRG groups, with a significantly greater reduction in Ca19–9 observed in the favourable TRG group [median -1, 862 U/mL (IQR: -7, 028 U/mL to -121U/mL)] compared to the unfavourable TRG group [median -194 U/mL (-635 U/mL to -3.9 U/mL); p=0.011). There was no significant difference in the chemotherapy regime, number of cycles or number of patients who had a dose reduction due to adverse effects. The time from diagnosis to chemotherapy and time from end of chemotherapy to surgery were also similar. Conclusions: In this small retrospective study, a greater reduction in Ca19–9 was significantly associated with a favourable TRG, which has been associated with improved survival. Patient numbers are limited due to the recent introduction of regression grading to pathology reporting guidelines so multicentre collaboration should be encouraged to identify more factors associated with favourable tumour regression. Translational research may also be able to identify other factors (e.g. gene expression) which are associated with favourable tumour regression.